Challenges and care strategies associated with the admission to nursing homes in Germany: a scoping review - Skudlik, Stefanie; Hirt, Julian; Döringer, Tobias; Thalhammer, Regina; Lüftl, Katharina; Prodinger, Birgit; Müller, Martin (BMC nursing, 2023)
Nursing home, Admission, Challenges, Care strategies, Participation, Older adults, Scoping review